Antioxidant, α-Glucosidase Inhibitory Activity and Molecular Docking Study of Gallic Acid, Quercetin and Rutin: A Comparative Study - Agus Limanto; Adelina Simamora; Adit Widodo Santoso; Kris Herawan Timotius (Molecular and Cellular Biomedical Sciences, 2019)
Background: Plant-phenolics and flavonoids, including gallic acid, quercetin and rutin, are considered as safe inhibitors for α-glucosidase. This study aimed to compare antioxidant and α-glucosidase inhibitory activities of gallic acid (GA), quercetin (QUE) and rutin (RUT).Materials and Methods: Pure compounds of GA, QUE, and RUT were used. Their antioxidant and inhibitory activity on α-glucosidase were investigated spectroscopically, including their kinetic analysis and interaction mechanism by docking simulation.Results: All the tested compounds (GA, QUE, and RUT) showed good antioxidant activity better than the standards ascorbic acid (AA) and butylated hydroxytoluene (BHT), with QUE showing the highest antioxidant activity based on 2,2-diphenyl1-picrylhydrazyl (DPPH) radical scavenging activity. Based on their reducing properties, the activities of the compounds follow the following order: AA > GA > BHT > QUE > RUT. Both GA and RUT induced a competitive type of inhibition, with activities stronger than acarbose (IC50 = 823 μg/mL), whereas QUE inhibited in a mixed type manner. The IC50 of GA, QUE, and RUT were 220.12, 65.52, and 224.55 μg/mL respectively. The results obtained from molecular docking indicate that all compounds have affinity in the active site pocket of α-glucosidase, with the hydrogen bond being the major force involved in each compound binding to the enzyme.Conclusion: In conclusion, QUE has better antioxidant and α-glucosidase inhibitory activity than GA and RUT. This work provides insights into the interactions between GA, QUE, and RUT and α-glucosidase.Keywords: docking, gallic acid, α-glucosidase, rutin, quercetin